Analysis of Student Ability to Develop ICT-Based Teaching Materials (Case Study in Biology Education Study Program UIN Syarif Hidayatullah Jakarta) - Baiq Hana Susanti (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2018)
Global competitions require human resources that have competitive advantages, including in the field of education. UIN biology education program has responded by developing ICT-based lecture system. The development of the most up-to-date courses is e-learning, which is one of the learning system which use communication and information technology. Learning object becomes very important part. Students become accustomed to utilize the various learning sources available online. On the other hand, the ability to develop teaching materials is one of the required skill as professional teachers. The research purpose was to obtain more information about the ability of students to develop ICT-based teaching materials. This research used descriptive qualitative method, the assessment of teaching materials developed by students done before and after the lecture. The subject of research was the 25 students who were enrolled in Vertebrata courses. The validity of the teaching materials assessed by experts using specific instrument, students respond data also collected using questionnaire.The results showed that the average value given by the expert validators was 83 that fall into good category. While the average response of students to teaching materials fall into moderate category. Teaching materials developed by students before and after the lecture also showed significant changes. Before the lecture, all teaching materials developed by students are still in the form of power point. After attending lectures, the types of teaching materials developed by the students were varied. Those consist of wordpress (24%), wix (20%), webnode (12%), prezi (12%), android (8%), macromedia 3D Presentation, Power Point Inspiring, and Website UIN respectively by 4%. Keywords: ICT-based learning materials, learning object, e-learning.